2020
DOI: 10.1016/j.virol.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The novel coronavirus Disease-2019 (COVID-19): Mechanism of action, detection and recent therapeutic strategies

Abstract: Novel coronavirus SARS-CoV-2, designated as COVID-19 by the World Health Organization (WHO) on the February 11, 2020, is one of the highly pathogenic β‐coronaviruses which infects human. Early diagnosis of COVID-19 is the most critical step to treat infection. The diagnostic tools are generally molecular methods, serology and viral culture. Recently CRISPR-based method has been investigated to diagnose and treat coronavirus infection. The emergence of 2019-nCoV during the influenza season, has led to the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
149
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(183 citation statements)
references
References 73 publications
(117 reference statements)
0
149
0
6
Order By: Relevance
“…The results of SARS outbreak showed that 18%‐57% of the treatment staff experienced emotional distress in the entire period of infection 30 . Huang et al studied the outbreak of generalized anxiety disorder and the depressive symptoms of COVID‐19 on 7,236 Chinese people; their results revealed the significant impact of COVID‐19 pandemic on the mental health of the participants 31 …”
Section: Discussionmentioning
confidence: 99%
“…The results of SARS outbreak showed that 18%‐57% of the treatment staff experienced emotional distress in the entire period of infection 30 . Huang et al studied the outbreak of generalized anxiety disorder and the depressive symptoms of COVID‐19 on 7,236 Chinese people; their results revealed the significant impact of COVID‐19 pandemic on the mental health of the participants 31 …”
Section: Discussionmentioning
confidence: 99%
“…Remdesivir, possessing an analogous structure to inhibitors of HIV reverse transcriptase, is reportedly under clinical trials for curing 2019-nCoV ailment [ 62 ]. For the prevention of coronavirus diseases such as acute influenza, the use of Ribavirin and Fabiravir in combination with Oseltamivir shows a greater impact than that of Oseltamivir alone [ 63 ]. In peracute hypoxaemia, symptoms can be successfully mitigated by combining antibiotics, lopinavir, alpha-interferon and providing mechanical ventilation [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like some other coronaviruses, SARS-Coronavirus-2 is also a family of coronaviridae, which is genomically composed by the structural as well as non-structural proteins. This is an RNA virus in which on one hand, the structural protein contains S protein (spike), M protein (membrane), E protein (envelope), and N protein (nucleocapsid) [6] . On the other hand, the non-structural protein (NSP) is an open reading frame (ORF) consisting of NSP1-16 [7] .…”
Section: Introductionmentioning
confidence: 99%